AN EXPERIMENT ON FLUID MECHANICS IN A VIRTUALREALITY (International Journal of Food and Nutritional Sciences, 2022)
Physical sub-areas aremathematically studied in several disciplines ofstudy to provide students the skills they need forprofessional optimization